2010
DOI: 10.3109/17435390.2010.530004
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells contribute to altered vascular reactivity and ischemia-reperfusion injury following cerium oxide nanoparticle instillation

Abstract: Cerium oxide (CeO2) represents an important nanomaterial with wide ranging applications. However, little is known regarding how CeO2 exposure may influence pulmonary or systemic inflammation. Furthermore, how mast cells would influence inflammatory responses to a nanoparticle exposure is unknown. We thus compared pulmonary and cardiovascular responses between C57BL/6 and B6.Cg-KitW-sh mast cell deficient mice following CeO2 nanoparticle instillation. C57BL/6 mice instilled with CeO2 exhibited mild pulmonary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 42 publications
1
71
0
2
Order By: Relevance
“…Moreover, this time point is identical to the one used recently to assess the role of mast cells in vascular reactivity and ischemia reperfusion injury following IT administration of CeO 2 NPs. 34 These data show that acute administration of CeO 2 NPs caused a dose-dependent infiltration of neutrophils and macrophages, which caused an expansion of the alveolar interstitial space. Some CeO 2 NPs were engulfed by macrophages, and others gained access to the interstitium.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, this time point is identical to the one used recently to assess the role of mast cells in vascular reactivity and ischemia reperfusion injury following IT administration of CeO 2 NPs. 34 These data show that acute administration of CeO 2 NPs caused a dose-dependent infiltration of neutrophils and macrophages, which caused an expansion of the alveolar interstitial space. Some CeO 2 NPs were engulfed by macrophages, and others gained access to the interstitium.…”
mentioning
confidence: 69%
“…32,33 The doses of particles used in the present study are comparable with those employed in previous animal models of IT administration of CeO 2 NPs. 12,34 In a previous study, it has been demonstrated that acute (24 hours) exposure of mice to DEPs causes impairment …”
Section: Discussionmentioning
confidence: 99%
“…Particularly, studies related to in vivo interaction of NPs with mast cells are limited to clinical reports only 6 . Mast cells are derived from hematopoeitic precursor cells in the bone marrow and once they attain maturity migrate to the connective tissues of the body 7 .…”
Section: Introductionmentioning
confidence: 99%
“…DEX is known to elicit IgG and IgE antibody-mediated reactions and this could be correlated to the increased mast cells in DEX-SPIONS group in lungs. It has been shown that inhalation of cerium oxide nanoparticles can activate mast cells by promoting the release of TH 2 proinflammatory cytokines and resulting in altered vascular reactivity6 . Furthermore, carbon nanotube induced toxicities are mediated by mast cell activation in both the pulmonary and cardiovascular system55 .…”
mentioning
confidence: 99%
“…12 , 16 -18 As an example, we discuss the use of Raman spectroscopy in elucidating the biodistribution and immune response of CeO 2 NPs. 18 The risk of CeO 2 NP exposure is signifi cant since they are widely used in many applications, including solar cells and as fuel additives. Instillation of CeO 2 NPs in the lungs of mice was shown to activate mast cells, which play an important role in allergic immune responses, tissue repair, and the maintenance of homeostasis.…”
mentioning
confidence: 99%